A Comparative Study: Return and Risk Measurement Gold versus Islamic Mutual Fund - Anita Anita; Srawut Aree (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2022)
This study aims to determine the comparison between the return and risk of metal “gold” investment with the return of Islamic mutual fund during the period 2011 to 2019. The information Using data of gold prices and Net Asset Value (NAV) for the daily period. This study exploits the purposive sampling techniques and obtained 5 islamic mutual fund companies. This research applied an independent t-Test to Compare the return of the two investment instruments by Mann-Whitney. Test and result prove that there are differences at alpha 0,05. It was concluded that "gold" investment provides higher return than Islamic mutual fund but a non-significant difference in risk